2013
DOI: 10.1177/1074248413508003
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Early Reperfusion Injury With the Mitochondria-Targeting Peptide Bendavia

Abstract: We recently showed that Bendavia, a novel mitochondria-targeting peptide, reduced infarction and no-reflow across several experimental models. The purpose of this study was to determine the therapeutic timing and mechanism of action that underlie Bendavia’s cytoprotective property. In rabbits exposed to in vivo ischemia/reperfusion (30/180 min), Bendavia administered 20 min prior to reperfusion (0.05mg/kg/hr, i.v.) reduced myocardial infarct size by ~50% when administered for either 1 or 3 hours of reperfusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 67 publications
7
81
0
Order By: Relevance
“…24 Given its specificity and the abundance of preclinical data, we chose to include this peptide for the proof-of-principle studies. 38 SS-31 has proven effective in cultured renal tubular cells in which it preserved mitochondrial structure and accelerated ATP recovery upon reperfusion. 22 We extended these findings to human kidney tissue and found that incubation with SS-31 partially preserved respiratory chain complex I integrity upon simulated I/R.…”
Section: Discussionmentioning
confidence: 99%
“…24 Given its specificity and the abundance of preclinical data, we chose to include this peptide for the proof-of-principle studies. 38 SS-31 has proven effective in cultured renal tubular cells in which it preserved mitochondrial structure and accelerated ATP recovery upon reperfusion. 22 We extended these findings to human kidney tissue and found that incubation with SS-31 partially preserved respiratory chain complex I integrity upon simulated I/R.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiolipin plays a central role in cristae formation, MITO fusion, mtDNA stability and segregation and in the function and organization of the respiratory complexes into supercomplexes for oxidative phosphorylation (1014). Elamipretide has been shown to enhance ATP synthesis in multiple organs including heart, kidney, neurons and skeletal muscle (1519). This study, examined the effects of long-term therapy with elamipretide on LV and MITO function in dogs with HF.…”
mentioning
confidence: 99%
“…SS-31 interacts with cardiolipin via electrostatic and hydrophobic interactions, preventing cardiolipin induced conversion from cytochrome c into a peroxidase while protecting the electron transporting function (Szeto, 2014). So far, SS-31 has not been studied in models of primary mitochondrial disorders but beneficial effects were shown under conditions of mtDNA mutation (Dai et al, 2010) and myocardial damage (Brown et al, 2014;Dai et al, 2014;Kloner et al, 2012).…”
Section: Cardiolipin-targeted Antioxidantsmentioning
confidence: 97%